2016
DOI: 10.5781/jwj.2016.34.2.30
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Various Factors on the Brazed Joint Properties in Al Brazing Technology

Abstract: Last few decades have seen a rapid increase in the fabrication and characterization of Al alloys for automobiles, heat exchangers and aerospace industries. Aluminium alloys are popular because of their high specific strength, light weight, excellent wear and high oxidation resistance. The development of aluminium alloys in these applications makes their study and research of utmost importance. Brazing is applied to the aluminium alloys for joining various aluminium parts together in most of the industrial appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Dark layer from stainless steel side and light color layer from aluminum side can be noticed. Every layer contains number of phases depending on diffusion of elements between base metals and filler alloy [8] .…”
Section: Brazing Joint Microstructurementioning
confidence: 99%
“…Dark layer from stainless steel side and light color layer from aluminum side can be noticed. Every layer contains number of phases depending on diffusion of elements between base metals and filler alloy [8] .…”
Section: Brazing Joint Microstructurementioning
confidence: 99%
“…The active brazing was conducted at a 750 °C for 30 min in a vacuum furnace. The average compressive strengths of five samples were 1477 MPa, which means a favorable joint strength [7]. Additionally, the authors reported a maximum shear strength of 15 MPa for Cu/Al 2 O 3 joint when brazed with AgCuTiSn filler metal [8].…”
Section: Introductionmentioning
confidence: 88%
“…To further improve the properties of Al-alloys, wide investigations have been performed by the addition of alloying elements, impurity addition, and by using modifiers etc. [25][26][27] . The additional alloying elements may cause the development of IMCs, hence these IMCs are the key elements in accessing the microstructure and mechanical properties of Al-alloys.…”
Section: Low-temperature Al-based Brazing Fillersmentioning
confidence: 99%